Pediatric dermatology - Cohen, Bernard, 1951-; ClinicalKey eBooks ([Philadelphia] : Saunders/Elsevier, 2013)
Clinically focused and practical, this diagnostic reference is ideal for anyone who treats children with skin disorders. Over 800 top-quality full-color illustrations, balanced by clear and succinct text, deliver the right amount of clinical detail to help readers identify a wide range of diseases. Plus, summary tables and differential diagnosis algorithms help simplify diagnosis.
Introduction to Pediatric Dermatology -- Neonatal Dermatology -- Papulosquamous Eruptions -- Vesiculopustular Eruptions -- Nodules and Tumors -- Disorders of Pigmentation -- Reactive Erythema -- Disorders of the Hair and Nails -- Oral Cavity -- Factitial Dermatoses.
Expert consult.
Print version record.
Elsevier
Elsevier
Keywords: Pediatric dermatology; MEDICAL -- Gynecology & Obstetrics; Pediatric dermatology; Child; Skin Diseases -- Atlases; Infant; Skin Manifestations -- Atlases; Electronic books